2012
DOI: 10.1096/fasebj.26.1_supplement.1097.4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of complement activation attenuates placental ischemia‐induced hypertension in rat

Abstract: Preeclampsia is characterized by compromised placental perfusion and new onset hypertension during pregnancy. The complement system is part of the innate immune system and complement activation is known to increase in preeclampsia.HypothesisComplement activation is critical for placental ischemia‐induced hypertension. To test the hypothesis, we used the reduced uteroplacental perfusion pressure (RUPP) model of placental ischemia to induce hypertension and determined the effect of inhibiting complement activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Notably, the aberrant placentation process may be reversed by inhibiting the complement pathway using inhibitors at the maternal–foetal interface. The study by Lillegard et al [ 65 ] reported the relationship between complement activation and pregnancy hypertension, where complement inhibition slowed the evolution of high blood pressure following placental ischaemia in a rat model [ 65 ]. Furthermore, complications may arise if the complement system fails to remove ischaemic placental components [ 57 ].…”
Section: The Complement System In Preeclampsiamentioning
confidence: 99%
“…Notably, the aberrant placentation process may be reversed by inhibiting the complement pathway using inhibitors at the maternal–foetal interface. The study by Lillegard et al [ 65 ] reported the relationship between complement activation and pregnancy hypertension, where complement inhibition slowed the evolution of high blood pressure following placental ischaemia in a rat model [ 65 ]. Furthermore, complications may arise if the complement system fails to remove ischaemic placental components [ 57 ].…”
Section: The Complement System In Preeclampsiamentioning
confidence: 99%